Employment of acoustic field for pollutant emission reduction under lean combustion - Marcel Martins Alves (2011)
Pulsating combustion is a technique that directly intervenes in combustion processes modifying pollutant emissions and increasing thermal efficiency by varying pressure and temperature in the flame region. The pulsations accelerate mixture rate between oxidant and fuel, resulting in a more intense combustion process, with low fuel waste and potential for low emission of pollutants originated by partial combustion, such as carbon monoxide, unburned hydrocarbons, and soot. The flame structure is modified by introducing an acoustic field in the process, and the flame has its color changed from yellowish, with a high formation of soot, to bluish. This bluish color of the flame is a feature of premixed flames. The main focus of this work is to use acoustic field in order to promote a homogeneous mixture between oxidant and natural gas under extremely lean conditions, thereby trying to conciliate low emissions of both incomplete combustion products and NOx. Besides, a preliminary study was carried out in order to figure out how combustion instabilities could affect the combustion process. It was verified that combustion instability occurrence is strongly influenced by energy availability and flame velocity. Moreover, when considering pollutant emissions, it was noticed that when the maximum acoustic velocity overcame the flow velocity, there was inversion of pollutant emission behavior due to flow reversibility and deceleration. Therefore, acoustic displacement is the most important parameter to understand and control pollutant emissions. Furthermore, at some conditions, especially at low frequency, it was possible to reduce partial combustion product emissions without prompting NOx formation. .